2021
DOI: 10.1038/s41598-021-87605-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patterns of cave-exiting activity of hibernating bats in western North America

Abstract: Understanding frequency and variation of cave-exiting activity after arousal from torpor of hibernating bats is important for bat ecology and conservation, especially considering white-nose syndrome. In winter from 2011 to 2018, we acoustically monitored, and counted in hibernacula, two species of conservation concern—western small-footed myotis (Myotis ciliolabrum) and Townsend’s big-eared bats (Corynorhinus townsendii)—in 9 caves located in important habitat for these species in western North America. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 81 publications
2
3
1
Order By: Relevance
“…Our results support precipitation as an important factor for this species at multiple life phases. Elevation is another important variable contributing to the hibernacula models, with suitability increasing with elevation up to ~2750 m, consistent with previous studies of C. townsendii reporting the species hibernating at >1500 m (Gillies et al, 2014 ; Harris et al, 2019 ; Hayes et al, 2011 ; Szewczak et al, 1998 ; Whiting et al, 2021 ). However, recent modeling approaches predict higher suitability for C. townsendii hibernacula at elevations <1000 m. Differences in predicted elevation are likely due to differences in occurrence data, environmental predictor variables, study extent (including latitude), and modeling techniques used.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results support precipitation as an important factor for this species at multiple life phases. Elevation is another important variable contributing to the hibernacula models, with suitability increasing with elevation up to ~2750 m, consistent with previous studies of C. townsendii reporting the species hibernating at >1500 m (Gillies et al, 2014 ; Harris et al, 2019 ; Hayes et al, 2011 ; Szewczak et al, 1998 ; Whiting et al, 2021 ). However, recent modeling approaches predict higher suitability for C. townsendii hibernacula at elevations <1000 m. Differences in predicted elevation are likely due to differences in occurrence data, environmental predictor variables, study extent (including latitude), and modeling techniques used.…”
Section: Discussionsupporting
confidence: 82%
“…High humidity within hibernacula reduces evaporative water loss during hibernation (Speakman & Thomas, 2003). Our results support precipitation as an important factor for this species at reporting the species hibernating at >1500 m (Gillies et al, 2014;Harris et al, 2019;Hayes et al, 2011;Szewczak et al, 1998;Whiting et al, 2021). However, recent modeling approaches predict higher suitability for C. townsendii hibernacula at elevations <1000 m.…”
Section: Ecoregion Modelssupporting
confidence: 77%
“…The observed patterns in the distribution of minimum angle measurements for both left and right wings are in line with recent findings in the literature. as it has been reported that, the bats with fungal infestation exhibited restricted wing flexibility, leading to altered wing angles [40] . Our results align with this, as we observed a more widespread distribution of minimum angles in wings without fungal infestation, indicating greater morphological variability.…”
Section: Relationship Between Morphometric Parameters Of Bat Wingmentioning
confidence: 80%
“…Both species are of similar size and weight and form small to medium-sized nursery colonies in trees and buildings. It is suggested that small bat species may need to wake up more frequently to drink during hibernation due to an unfavorable surface-to-volume ratio 55 . Once an individual bat is active, it may have a high motivation to leave the hibernaculum to forage 56 and relocate to summer habitats.…”
Section: Discussionmentioning
confidence: 99%